2016
DOI: 10.1016/j.ccell.2016.01.006
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting p38 or MK2 Enhances the Anti-Leukemic Activity of Smac-Mimetics

Abstract: Birinapant is a smac-mimetic (SM) in clinical trials for treating cancer. SM antagonize inhibitor of apoptosis (IAP) proteins and simultaneously induce tumor necrosis factor (TNF) secretion to render cancers sensitive to TNF-induced killing. To enhance SM efficacy, we screened kinase inhibitors for their ability to increase TNF production of SM-treated cells. We showed that p38 inhibitors increased TNF induced by SM. Unexpectedly, even though p38 is required for Toll-like receptors to induce TNF, loss of p38 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 54 publications
9
54
0
1
Order By: Relevance
“…p38 and ERK signaling are implicated in AML cell proliferation (Birkenkamp et al, 1999). p38 inhibition enhances the anti-leukemic activity of Birinapant, a smac mimetic (Lalaoui et al, 2016). Besides MAPK inhibitors, HSP90 inhibitors suppress ERK signaling (Zong et al, 2015) and Rac inhibitors suppress p38 signaling (Zhang et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…p38 and ERK signaling are implicated in AML cell proliferation (Birkenkamp et al, 1999). p38 inhibition enhances the anti-leukemic activity of Birinapant, a smac mimetic (Lalaoui et al, 2016). Besides MAPK inhibitors, HSP90 inhibitors suppress ERK signaling (Zong et al, 2015) and Rac inhibitors suppress p38 signaling (Zhang et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…During TLR signaling, activation of the p38MAPK-MK2 pathway promotes the stabilization of TNF expression (58). In contrast, during ripoptosome signaling in myeloid leukemia cells, p38MAPK has been shown to inhibit TNF expression, and inhibition of MK2 results in enhanced cell death of leukemia cells (59). It was subsequently shown that MK2 mediates an inhibitory phosphorylation of RipK1, which restricts ripoptosome induced cell death (60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, several pharmaceutical compounds have been developed to target these kinases in auto-inflammatory diseases (Genovese, 2009). However, recently we proposed that the p38-MK2 axis also regulates TNF- and RIPK1-dependent SMAC-mimetic (SM)-induced cell death (Lalaoui et al., 2016). These results therefore suggest that TAK1 mediates its pro-survival effect, at least in part, through activation of p38-MK2 (Sakurai, 2012).…”
Section: Introductionmentioning
confidence: 99%